Reintegration of Islamic Education: New Direction for the Transformation of Madrasah Education - Muhammad Azzami; Sangkot Sirait; Muqowim Muqowim (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study explores strategies for transforming madrasah education through the reintegration of Islamic education to align foundational Islamic principles with contemporary educational needs. A qualitative approach was employed, utilizing a literature review and conceptual analysis to examine the assumptions underlying Islamic education and their contribution to the fragmentation of its core values. The findings indicate that the reintegration of Islamic education requires three key approaches: ideological criticism, historical analysis, and the adoption of a reintegration paradigm. These approaches provide a framework for presenting Islamic knowledge holistically, avoiding transformations that lack direction or merely reflect current realities. By integrating these approaches, madrasah education can maintain its foundational connection to Islamic principles while addressing modern challenges. This strategy offers a pathway to revitalizing Islamic education in a way that is both relevant and faithful to its core values. The proposed reintegration strategy provides a roadmap for transforming madrasah education, fostering a holistic approach that preserves its ideological roots and equips it to navigate contemporary realities effectively.